Simulation of Dissolved Oxygen Concentration in an Urban Lake Based on MLR and ARDL - ZHAO Hongcheng; YANG Fei; ZHOU Peng; GUO Jiacheng; HUANG Jinbai (Renmin Zhujiang)
Research on the simulation of dissolved oxygen (DO) in urban lakes is of significance in promoting the development of water quality simulation research for urban lakes. A lake, which is near the central area of Yangzhou City was adopted as the study area. Based on the observed data of DO, blue-green algae concentration, water temperature (WT), electric conductivity (EC), and pH in 2020, a multiple linear regression (MLR) model and an autoregressive distribution lag (ARDL) model were developed. Simulations for the observed sequence values of DO in 2020 (from January 1, 2020 to December 31, 2020) and four quarters of 2020 were carried out. The results indicate that the simulation results of the MLR model exhibit relatively low accuracy, while those of the ARDL model show relatively high accuracy; the coefficient of determination (R2) of the DO simulation results for different periods is 0.75–0.99. Both MLR and ARDL models have applicability for simulating DO in the lake. Specifically, the ARDL model has better applicability for DO sequence simulation with time period changes than MLR.